On the nine-point conic of hyperbolic triangles - Szilasi, Zoltán (Teaching Mathematics and Computer Science, 2025)
In the Cayley–Klein model, we review some basic results concerning the geometry of hyperbolic triangles. We introduce a new definition of the circumcircle of a hyperbolic triangle, guaranteed to exist in every case, and describe its main properties. Our central theorem establishes, by means of purely elementary projective geometric arguments, that a hyperbolic triangle has a nine-point conic if and only if it is a right triangle. Subject Classification: 51M09